Discordant frequencies of tissue‐resident and circulating CD180‐negative B cells in chronic rhinosinusitis. Issue 6 (25th February 2017) - Miljkovic, Dijana; Ou, Judy; Kirana, Chandra; Hulse, Kathryn E.; Hauben, Ehud; Psaltis, Alkis; Wormald, Peter‐John; Vreugde, Sarah
Abstract : Background: The unconventional toll‐like receptor (TLR) CD180 is implicated in chronic inflammatory diseases; however, its role in chronic rhinosinusitis (CRS) has yet to be investigated. Here we study the expression of CD180, its homologue TLR4 and myeloid differentiation factor 1 (MD1) on mucosal and systemic immune cell populations in relation to serum immunoglobulin G (IgG) levels. Methods: A total of 70 patients were recruited to the study. Mucosal and peripheral blood samples were prospectively collected from CRS patients and non‐CRS controls without evidence of sinus disease. The expression of TLR4, MD1, and CD180 was investigated using qualitative real‐time polymerase chain reaction (qRT‐PCR), immunohistochemistry, and flow cytometry. Serum IgG levels were determined using enzyme‐linked immunosorbent assay (ELISA). Results: CRS with nasal polyps (CRSwNP) patients had significantly increased messenger RNA (mRNA) expression of CD180 and MD1 compared to controls (5.54‐fold and 2.1‐fold, respectively, p < 0.01). B cells lacking CD180 were lower in CRSwNP tissue compared to CRS without nasal polyps (CRSsNP) and controls (21.07 ± 6.41 vs 41.61 ± 7.82 vs 40.06 ± 8.06; p < 0.01) but higher in blood (39.18 ± 8.3 vs 17.95 ± 7.82 and 12.49 ± 4.92; p ≤ 0.05). Conclusion: Changes in mucosal and peripheral CD180‐expressing B cells were identified in CRSwNP patients compared to CRSsNP and controls. This suggests a role for these cells in the dysregulated immune response in these patients.